Mitochondrial genome analysis of Ectophasia roundiventris (Diptera, Tachinidae) - Xin Li; Shuangmei Ding; Peng Hou; Xiaoyan Liu; Chuntian Zhang; Ding Yang (Mitochondrial DNA. Part B. Resources, 2017)
The mitochondrial genome of Ectophasia roundiventris (Loew, 1858), the first representative of subfamily Phasiinae, was sequenced and annotated. So far, there are four Tachinidae mitochondrial genomes, here, all of them are used in Neighbour-Join and Maximum Likelihood analyses. The nucleotide composition of Ectophasia roundiventris mitochondrial genome was 40.4% of A, 39.0% of T, 11.8% of C, 8.8% of G, 79.4% of A + T content. The codon ATG was the most popular start codon. The conservative stop codon was TAA, COX2, and ND5 terminated with an incomplete stop codon T, while the gene ND4 was ended with stop codon TA.